Aplicaciones avanzadas de los materiales compuestos en la obra civil y la edificación - A. Pérez, Marco (OmniaScience, 2014)
The purpose of this work is to provide a global view of the current state of the art and recent developments on the applicability of composite materials in civil engineering and construction. The book contains a collection of research papers from national and international experts, which address current and future challenges in this field, providing, through a wide variety of case studies, a roadmap with technical skills and knowledge practical tools for the use of composite materials in new applications. The texts are -as far as possible- self-contained in their parts, allowing a reading according to the particular interest of each reader. They present technical foundations, research results, and review and compile updated bibliographic references that complement and allow the reader to acquire a deeper knowledge of the topics exposed, directing it towards possible future lines of research. Written by professionals and researchers with experience in this field, this book aims to be a reference text for those not initiated in the subject and a study and research tool for readers of more advanced levels.